Variation in agronomic performance, cooking time and quality of high performing second-generation biofortified common bean in Democratic Republic of Congo (Agriculture, Food, and Natural Resources Journal, 2026)
Common bean (Phaseolus vulgaris L.) is a vital source of protein and micronutrients for millions of people in sub-Saharan Africa, yet adoption of improved varieties depends on both agronomic performance and consumer-preferred traits. The present study evaluated 285 second-generation biofortified common bean genotypes alongside five local checks at Butembo and Lukanga, Democratic Republic of Congo (DRC), during the 2022 long rain season. Farmer participatory selection was conducted at flowering and maturity stages, emphasizing vigor and pod number. Hydration coefficient, cooking time, integrity after cooking, and sensory evaluation of cooked beans were also assessed. Results showed that 124 biofortified genotypes were selected by farmers, with pod numbers ranging from 14 to 27 compared to 9–13 for local checks. Hydration coefficients were higher in biofortified genotypes (1.4–3.4) than in local varieties (1.7–2.0). Conversely, cooking times were shorter in biofortified genotypes (73–170 min) compared to local lines (120–144 min). A significant negative correlation (p < 0.001) was observed between hydration coefficient and cooking time. Sensory evaluation revealed acceptable taste, flavour, and starchiness for most biofortified genotypes, though some showed undesirable traits. Overall, biofortified genotypes combined large pod numbers with shorter cooking times, meeting both farmer and consumer preferences and hence being promising for adoption in Eastern DRC.
Keywords: Biofortification; Common bean; Cooking time; Farmer participatory selection